Acquisition Management - Engelbeck, R. (Berrett-Koehler Publishers, 2001)
Your Step-by-Step Guide to Today's Best Procurement Practices "Acquisition Management is a great book for those in the government acquisition business. It is complete and well documented. I was especially impressed with the format which makes it valuable for training people new to the acquisition field and as a reference to those with more experience." Brig. Gen. James C. Dever, Jr. USAF (Ret.) Formerly, DCS Contracting and Manufacturing, Air Force Systems Command Whether you're a contractor or government personnel, one thing is for sure: The federal procurement process is undergoing a major overhaul. And, to be successful, you must master a host of new methods, rules, and requirements. New from Management Concepts, Acquisition Management is the first step-by-step guide to the government's new strategies and methods for procurement. This new, streamlined acquisition process adopts the best practices of the business world to boost cost-efficiency and reduce the time from contract development to delivery. Acquisition Management prepares you fully to understand and apply these new acquisition techniques, teaching you how to manage contract risk and work more effectively as a member of a multi-functional team. Key Features " Reviews acquisition principles to help you develop a basis for decision-making " Gives you step-by-step guidance for every phase of the process, from solicitation to closeout " Places the procurement process in a risk management context to help you troubleshoot problems and ensure success " Outlines the roles and tasks of major players in the process to help you work more effectively as part of the contracting team " Presents pertinent information from the FAR at each applicable point in the acquisition process